2017
DOI: 10.1007/s00468-017-1648-x
|View full text |Cite
|
Sign up to set email alerts
|

Tree growth responses to changing temperatures across space and time: a fine-scale analysis at the treeline in the Swiss Alps

Abstract: Key messageTree growth shows a non-linear response to temperature. Under climate change, this leads to a consistent increase of high basal area increments only at the highest elevations. Abstract Forest dynamics and particularly tree growth rates are considerably affected by temperature. Hence, global warming is expected to have large impacts on the growth and distribution of trees, especially at the cold distribution limit. While the influence of interannual temperature variability on tree growth has been des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 51 publications
1
19
0
1
Order By: Relevance
“…In a study close to our site, similar seedling survival at low and high elevations suggested that the current treeline position lags behind climatic changes (Zurbriggen, Hättenschwiler, Frei, Hagedorn, & Bebi, 2013). This indicates that temperature limitation of growth has been reduced over the past few decades, as was also observed for other treelines in the Swiss Alps (Jochner, Bugmann, Nötzli, & Bigler, 2018).…”
Section: Growing Season Temperature Did Not Modulate the Fertilizersupporting
confidence: 80%
See 1 more Smart Citation
“…In a study close to our site, similar seedling survival at low and high elevations suggested that the current treeline position lags behind climatic changes (Zurbriggen, Hättenschwiler, Frei, Hagedorn, & Bebi, 2013). This indicates that temperature limitation of growth has been reduced over the past few decades, as was also observed for other treelines in the Swiss Alps (Jochner, Bugmann, Nötzli, & Bigler, 2018).…”
Section: Growing Season Temperature Did Not Modulate the Fertilizersupporting
confidence: 80%
“…Hence, despite a limitation of plant growth by low temperatures at high elevation, even a small improvement of nutrient supply, for instance by increased atmospheric deposition or enhanced nutrient mineralization in warmer soils, can cause changes in high elevation treeline ecosystems. Our experimental site and all “natural” treelines in the region experienced a 2 K warming over the past four decades, which has reduced thermal limitation of growth (Jochner et al, ) and may have masked interactions between fertilizer addition and more subtle year‐to‐year or spatial temperature differences. Thus, while treeline trees and associated dwarf shrubs benefit from nutrient addition in terms of growth, our results do not imply that nutrient availability influences the elevational position of the treeline.…”
Section: Discussionmentioning
confidence: 99%
“…Many works are focused on revealing the response of woody plants to a temperature increase at the upper limit of their growth, i.e. under the conditions of a clear limitation of growth by temperatures (Wang et al 2005;Jiao et al 2016;Jochner et al 2018). The majority of researchers observed reliable tree growth response to the variation of spring-summer air temperature (Naurzbaev and Vaganov 2000;Briffa et al 2004;Chen et al 2015;Wang et al 2015;Helama and Sutinen 2016;Zhang et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the sum of degree day from September to December (previous year) was associated to NDVI (Table , r = 0.59). It has been shown recently that over a fine scale in high‐elevation forests, degree day sum or the growing season length explains forest productivity better than averaged temperature (Jochner et al, ). The differential correlation of NDVI and RWI with climatic variables across site conditions partially confirms our second hypothesis that climatic influence varies spatially but further efforts must be done in enlarge NDVI databases to overcome possible spurious links between climate and remotely sensed variables (Tables S3 and S4).…”
Section: Discussionmentioning
confidence: 99%